E-RESUME MEDIS RAWAT INAP DALAM MENDUKUNG KLAIM INA-CBGS PASIEN TUBERCULOSIS DI RUMAH SAKIT - Puseng Manik; Johni S Pasaribu; Irda Sari; Jeri Sukmawijaya (Media Bina Ilmiah, 2023)
The development of information system technology is currently widely utilized in various aspects of life, one of which is the aspect of hospital services. The lack of information needed to fulfill the requirements of the Indonesia Case-Based Group (INA-(CBGS) claim for inpatient Tuberculosis patients has led to claim disputes, thus hampering the claim process for Tuberculosis patients in the hospital. This study aims to design an electronic-based medical resume to support the INA-CBGs claim process in hospitals to minimize claim disputes. The Extreme Programming method was chosen because it is suitable for developing systems quickly, and the results are easier to adjust in the system development process. Based on system testing using the black-box method, the designed medical e-resume system can minimize the occurrence of claim disputes in hospitals